Proposal for a medical record architecture using Alexa and Standard HL7 - González Ávila, Nicol; López Martínez, Ignacio; Olivares Zepahua, Beatriz Alejandra; Muñoz Contreras, Hilarión; Suárez Gutiérrez, Manuel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
Virtual Assistants are tools that facilitate user interaction through natural language; they are integrated with artificialintelligence. Currently, these technologies are used for the development of applications or skills, better known as Skill’s. In this sense, and referring to the Alexa Assistant, using a physical device Echo Show, from the company to which the mentioned tool belongs and articulates to health-oriented standards for the creation of electronic medical records to support health personnel. In addition, a version of the standards is going to be used by Health Level Seven (HL7), an organization dedicated to the development of health-oriented standards that will be used. In consequence, the creation of the skills is based on the JavaScript object notation (JSON) for data exchange, the module was worked under the Model-View-Controller architecture. As result, the present work shows the proposed architecture for the module of an electronicmedical record.